2014
DOI: 10.1016/j.jaac.2013.11.010
|View full text |Cite
|
Sign up to set email alerts
|

24- and 36-Week Outcomes for the Child/Adolescent Anxiety Multimodal Study (CAMS)

Abstract: Objective We report active treatment group differences on response and remission rates and changes in anxiety severity at weeks 24 and 36 for the Child/Adolescent Anxiety Multimodal Study (CAMS). Method CAMS youth (N=488; 74%≤12 years) with DSM-IV separation, generalized, or social anxiety disorder were randomized to 12 weeks of cognitive behavior therapy (CBT), sertraline (SRT), CBT+SRT (COMB), or medication management/pill placebo (PBO). Responders attended 6 monthly booster sessions in their assigned trea… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

7
75
3
2

Year Published

2015
2015
2020
2020

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 144 publications
(87 citation statements)
references
References 27 publications
7
75
3
2
Order By: Relevance
“…She graduates out of cognitive behavioral therapy and endorses depressive symptom remission in monthly then in every 3-month follow-ups. Ten months later, Emma, her parents, and Dr Smith [43][44][45][46] Only a few medications are FDA-approved for use in the pediatric population, so that much of the psychopharmacologic prescribing for pediatric depression and all of the prescribing for non-obsessive-compulsive disorder anxiety are considered off-label. Although most SSRIs are considered equivalent, paroxetine is disfavored in the pediatric population because of its efficacy and side-effect profile [47][48][49] Research does not support the use of SSRIs as first-line treatment of symptoms of posttraumatic stress disorder, although, in practice, they are commonly used as an adjunctive therapy.…”
mentioning
confidence: 99%
“…She graduates out of cognitive behavioral therapy and endorses depressive symptom remission in monthly then in every 3-month follow-ups. Ten months later, Emma, her parents, and Dr Smith [43][44][45][46] Only a few medications are FDA-approved for use in the pediatric population, so that much of the psychopharmacologic prescribing for pediatric depression and all of the prescribing for non-obsessive-compulsive disorder anxiety are considered off-label. Although most SSRIs are considered equivalent, paroxetine is disfavored in the pediatric population because of its efficacy and side-effect profile [47][48][49] Research does not support the use of SSRIs as first-line treatment of symptoms of posttraumatic stress disorder, although, in practice, they are commonly used as an adjunctive therapy.…”
mentioning
confidence: 99%
“…2013, Wergeland ve ark. 2014, Piacentini ve ark. 2014 Toparlanacak olursa, hem BDT hem de ilaç tedavisi, çocuk-luk çağı kaygı bozukluklarının belirtileri üzerinde anlamlı bir iyiye gidiş sağlamakla beraber, bu iki tedavi birleştirilerek yaklaşıldığında, sağaltımın anlamlı biçimde daha etkili olduğu gözlenmiştir.…”
Section: İşlemunclassified
“…12 haftalık ve 36 haftalık izlemde de sonuçların değişmediği yayınlanan iki araştırma ile gösterilmiştir (Ginsburg ve ark. 2011, Piacentini ve ark. 2014).…”
Section: Introductionunclassified
“…Each treatment on its own is effective for young people with anxiety disorders, but a combination of SSRIs and CBT has been found to be more effective than mono-therapies, with this difference decreasing over time [3]. However, pharmacological treatment is not recommended as a first line as there is a potential risk of harm to children and young people [2].…”
Section: Introductionmentioning
confidence: 99%
“…Several studies have shown maintenance of gains one year post treatment [15][16][17]; and including youth 2-3 years [3], 3.5 years [18], 6 years [19] and 7.4 years [20] following treatment cessation. Assessing outcomes over the long term may be particularly indicated among children treated with ACT as studies of ACT for children with a spectrum of presenting problems have found that treatment gains were either not fully evident at posttreatment (or initial follow-up), or that greater improvements for ACT were obtained some months after therapy cessation [21][22][23].…”
Section: Introductionmentioning
confidence: 99%